Vol.2 - "Goodwin, Matthew Oliver" (New Delhi, 2004)
Numerology, the simplest of the occult sciences to master, offers deep insights into the personality. You can use numerology to understand yourself, friends, associates and lovers. You can see the dynamics of relationships and you can determine the best time to marry, change jobs, move, invest and travel. Here is the definitive work on Numerology. Organized for clarity that a beginner can grasp easily and detailed so that the advanced student will find useful new information. This volume is designed as a working manual. Among its features are many examples, detailed working charts containing all the information needed, and some new material on the meanings of the Master Numbers and Doubled Numbers.
Keywords: Numerology